2017
DOI: 10.1016/j.mechmat.2017.06.009
|View full text |Cite
|
Sign up to set email alerts
|

In-situ investigation of dynamic deformation in NiTi shape memory alloys under laser induced shock

Abstract: The free surface particle velocity of NiTi target shocked with a pulsed laser beam was measured with a photonic Doppler velocimetry (PDV) system to study the dynamic deformation behavior of NiTi alloys at ultra-high strain rate of 10 6 ∼10 7 /s. Through the analysis of the particle velocity profiles, the shock wave intensity was found to have the influence on the process of austenite-martensite transformation. Theoretical analysis of shock wave propagation showed that the first plateau in the velocity profile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…However, the stress plateau gradually disappears with an increasing strain rate, which has been confirmed by Nemat-Nasser S. et al [48,49]. Wang et al provided direct experimental evidence that stress-induced martensite transformation occurs in NiTi SMA undergoing laser-shock peening, where the strain rate is approximately 10 7 s −1 [50,51]. It is concluded that the mechanism of stress-induced martensite transformation at an ultra-high strain rate is obviously different from that at a low strain rate.…”
Section: Resultsmentioning
confidence: 72%
“…However, the stress plateau gradually disappears with an increasing strain rate, which has been confirmed by Nemat-Nasser S. et al [48,49]. Wang et al provided direct experimental evidence that stress-induced martensite transformation occurs in NiTi SMA undergoing laser-shock peening, where the strain rate is approximately 10 7 s −1 [50,51]. It is concluded that the mechanism of stress-induced martensite transformation at an ultra-high strain rate is obviously different from that at a low strain rate.…”
Section: Resultsmentioning
confidence: 72%
“…Many researchers have demonstrated that stress-induced martensitic phase transformation of NiTi shape-memory alloys may occur during tensile, compressive, and shear loading [ 32 , 33 , 34 ]. Wang et al [ 35 , 36 ] provided experimental evidence that NiTi shape-memory alloys undergo stress-induced martensitic transformation when subjected to laser impact strengthening, and its strain rate is about 10 7 s −1 . Their results suggest that the mechanism of stress-induced martensitic phase transformation at ultra-high strain rates is significantly different from that at low strain rates.…”
Section: Resultsmentioning
confidence: 99%
“…Martensite variants can be twinned (M t ) and de-twinned (M d ). The reversible transformation from austenite to martensite [46] and vice versa results in SMA behavior [49], and it is known that the martensitic transformation can be caused by both temperature and stress [50], which are referred to as SME and pseudoelasticity, respectively [51][52][53]. The essential actuating ability of the NiTi SMA heat engine is a consequence of the pseudoelastic and SME of SMA material.…”
Section: Phase Transformation In Smamentioning
confidence: 99%